(untitled) (Research, Society and Development, 2022)
The education of deaf students is an agenda that must always be addressed when talking about inclusion, especially within the school. For a long time, deaf people were socially excluded because they were unable to communicate orally, but over the years and the perception of beings capable of learning and interacting, society created ways to communicate and include the deaf, with the advancement of technology, this process becomes increasingly easier, however, when referring to school, the lack of knowledge about these technological means can be a problem and end up leaving them aside. Thus, the article presented here is about the investigation and suggestion of ways to use these new technologies in the teaching and learning process of deaf students, making them facilitators of inclusive education. Using analysis of Brazilian legislation and scientific articles that address the subject, so that you can understand the process of education of the deaf and the technologies that can be used, and thus contribute to an inclusive pedagogical work.